The Holmes Concession and the British-American Rivalry for Bahrain’s Oil (1925-1929) (658/676, 1260/1277 AD) - Husham Ali Obai; Dr. Imad Jassim Hasan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Oil is one of the discoveries in the modern era that was able to change the map of the world and one of the most important causes of global conflict, and whoever owns oil has become an important source of economic power, as he was able to transform countries from a tribal agricultural society to a civilized industrial society, but the presence of oil in the lands of (a country ) does not mean its transformation into an industrial country, because the presence of oil without investing it does not give the desired benefit from its existence, so the oil industry, oil is one of the industries that require large capital for surveying, exploration and drilling operations, up to the stage of extraction and then export, so the oil countries, including Bahrain, resorted To foreign companies because they lacked money and experience at the beginning of its discovery, and traced its importance as being an important source of energy and raw material for many industries, in addition to being the most important source of income for the Emirate of Bahrain. In fact, the concession in 1925 granted by the ruler of Bahrain, Sheikh Hamad bin Isa Al Khalifa It is the first oil concession that led to the development of the oil industry and economic and social development during period of (46) years, and then changed many issues related to the political and economic aspects. And the entry of Bahrain into a new phase in its contemporary history.